2021
DOI: 10.1039/d1ta06863f
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing polysulfide confinement and conversion in meso-/microporous core–shelled MoC/NC microspheres for lithium–sulfur batteries

Abstract: A core–shelled MoC/NC microsphere with a mesoporous core and a microporous-thin shell serves as a multi-functional sulfur host to enhance polysulfide confinement and conversion in lithium–sulfur batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Therefore, the electrochemical reaction process of the sulfur cathode can be limited to narrow pores, and micropores can effectively restrain the shuttle of polysulfides through physical constraints so that the composites have good reversibility and high rate discharge ability. 97–99 At the same time, the microporous carbon-supported sulfur cathodes manifest different electrochemical behavior from their traditional sulfur counterparts. The conventional sulfur cathode shows two platforms at about 2.4 and 2.1 V vs. Li + /Li during the first discharge, 100,101 while the microporous carbon-supported sulfur cathode showed only a single platform at 1.8 V vs. Li + /Li.…”
Section: Natural Porous Bdc-based Hostsmentioning
confidence: 99%
“…Therefore, the electrochemical reaction process of the sulfur cathode can be limited to narrow pores, and micropores can effectively restrain the shuttle of polysulfides through physical constraints so that the composites have good reversibility and high rate discharge ability. 97–99 At the same time, the microporous carbon-supported sulfur cathodes manifest different electrochemical behavior from their traditional sulfur counterparts. The conventional sulfur cathode shows two platforms at about 2.4 and 2.1 V vs. Li + /Li during the first discharge, 100,101 while the microporous carbon-supported sulfur cathode showed only a single platform at 1.8 V vs. Li + /Li.…”
Section: Natural Porous Bdc-based Hostsmentioning
confidence: 99%
“…41 It has been demonstrated that the electrical conductivity of TMOs can be improved by dopamine coating and subsequent carbonization treatment. [42][43][44] In addition, nanosheets or the hollow structure can effectively improve the surface area of TMOs, thus enhancing the adsorption and catalytic sites to LiPSs of TMOs. [45][46][47] Moreover, the hollow structure can alleviate the volume expansion during the reduction process of LiPSs, thus improving the cycling stability of Li-S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, micromesopores and voids inside the sulfur hosts are able to increase the loading and accommodate the volume-change, respectively. 20,21 Among various carbon-based sulfur hosts, graphene has good potential because of its high specific surface area, mechanical strength, good conductivity and flexibility. 22,23 Cao et al coated nano-sulfur on graphene oxide sheets (GOSs) by using a redox reaction between sodium thiosulfate and hydrochloric acid, which exhibited stable electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, micro–mesopores and voids inside the sulfur hosts are able to increase the loading and accommodate the volume-change, respectively. 20,21…”
Section: Introductionmentioning
confidence: 99%